Proses Tour Guide dalam menangani Wisatawan Kelelahan Fisik pada Destinasi Taman Wisata Alam Kawah Ijen - Achmad Farihul Karim (Fakultas Ilmu Sosial dan Ilmu Politik, 2026)
This study aims to determine the role of tour guides in handling tourists experiencing physical fatigue at Taman Wisata Alam Kawah Ijen. Kawah Ijen is one of the natural tourist destinations with challenging trekking routes, making tourists vulnerable to physical fatigue during the trip. In this condition, tour guides play an important role in maintaining tourists’ safety, comfort, and the smoothness of tourism activities.This research used a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The research informants consisted of tour guides and tourists participating in tours with Visitbanyuwangi.id. The results showed that the duties of tour guides in handling physically exhausted tourists include giving briefings before climbing, monitoring tourists’ physical conditions during the trip, arranging rest periods, providing simple first aid, and motivating tourists. In addition, tour guides also educate tourists about the importance of physical preparation and travel safety before the climb.The conclusion of this study indicates that tour guides have a very important role in minimizing the risk of tourists’ physical fatigue so that tourism activities can run safely, comfortably, and smoothly. The professionalism and readiness of tour guides are the main factors in creating a positive travel experience for tourists.
Validasi dan Finalisasi Ratna 20 Juli 2026
Keywords: Kawah Ijen; Physical Fatigue; Tour Guide; Tourist